The Adoption of ChatGPT in SME Human Resource Practices: Integrating TOE–TAM with Trust as a Mediator and Religiosity as a Moderator - Hanung Eka Atmaja; Suddin Lada; Shinta Ratnawati; Miftachul Mujib; Satrio Tegar Sadewo; Raina Dewi Aldianti (Vifada Management and Social Sciences, 2026)
Purpose: The development of artificial intelligence technology, particularly ChatGPT, presents both opportunities and challenges for Small and Medium-sized Enterprises (SMEs) in enhancing the efficiency of human resource management practices. However, the level of adoption of this technology is still influenced by various complex factors, not only technical but also psychological and individual values. This study aims to analyse the factors influencing the adoption of ChatGPT in SMEs through the integration of the Technology–Organisation–Environment (TOE) framework and the Technology Acceptance Model (TAM), whilst considering the mediating role of trust and the moderating role of religiosity. Research Design and Methodology: This study employs a quantitative approach using a survey method targeting SME operators in Central Java, East Java, and the Special Region of Yogyakarta (DIY). The sampling technique utilised purposive sampling, with a sample size of 200 SME operators meeting the study criteria. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with the assistance of SmartPLS software. Findings and Discussion: The results indicate that technological, organisational, and environmental factors, as well as perceptions of ease and utility, play a role in shaping trust in ChatGPT. This trust serves as the primary determinant in driving technology adoption, whilst religiosity was found to strengthen the relationship between trust and usage decisions. These findings confirm that ChatGPT adoption among SMEs is influenced not only by functional aspects but also by psychological factors and individual values. Implications: The implications of this research contribute to the development of a more context-specific technology adoption model based on artificial intelligence, whilst providing practical recommendations for SME stakeholders, technology developers, and policymakers in promoting the effective and sustainable utilisation of ChatGPT.